HAK CUTI HAID, HAMIL, DAN MELAHIRKAN PEKERJA PEREMPUAN DALAM UNDANG-UNDANG KETENAGAKERJAAN DAN OMNIBUS LAW CIPTA KERJA PERSPEKTIF MAQASHID SYARI’AH IBNU ASHUR - Anusantari, Inama Ma; Nur, Iffatin (IAIN Tulungagung, 2021)
Omnibus Law on Cipta Kerja has received a variety of strong reactions from various activists and womens’ advocacy institutions. They claim that the articles on the right to leave menstruation, pregnancy, miscarriages and childbirth for women workers have been abolished of the Omnibus Law on Employment Law. Whereas before the leave rights for women workers in certain circumstances have been neatly codified in the Manpower Act. Even though the Minister of Manpower has denied this, the absence of leave rights for women workers in certain circumstances in the Omnibus Law on Employment Copyright will provide the potential for violation of leave rights for women workers. This paper uses the theory of maqashid sharia Ibn ‘Ashur as material to study the potential violation of leave rights for women workers in certain circumstances. The reason for choosing Ibn ‘Ashur theory is because of this moderate and progressive mind. This paper uses the literature method with data sources in the form of written documents, namely accredited journals, books and online articles on the theme of writing. The results showed the potential violation of leave rights for women workers in certain circumstances in terms of the sharia maqashid Ibn ‘Ashur is very large. And this does not reflect the purpose of the shariah maqashid which is to safeguard religion, reason, soul, descent and wealth.